The Impact of The Joint Enterprise Group (KUBE) Program on Employment - Kurniawan, Randi; Abdur-Rabb, Ahmad Faqhruddin (Jurnal Ekonomi Pembangunan, 2025)
One of the community-based government initiatives aimed at expanding employment opportunities in Indonesia is the Joint Enterprise Group (KUBE). This study examines the impact of KUBE on individual employment outcomes using two waves of the Indonesia Family Life Survey (IFLS) data from 2007 and 2014. Employing the Difference-in-Difference (DID) technique, the analysis finds that the presence of KUBE in a community is associated with a higher probability of adults gaining employment. However, the positive effect is concentrated in the category of casual workers, while no significant effect is observed for other employment types such as self-employment or formal wage work. Interestingly, the existence of KUBE is also associated with a lower probability of individuals working as unpaid family labor. These findings suggest that KUBE has the potential to promote labor absorption in poor communities, particularly in informal sectors. Therefore, expanding KUBE’s coverage and integrating it with complementary policies could enhance its role in stimulating economic activity and improving community welfare.